Work-Life Balance Of Women Entrepreneurs (Wlbwe): A Model - Omar, Norliza; Jano, Zanariah; Ahamat, Amiruddin; Mat Aris, Azman; Al-Shami, Samer Ali Hussein (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Today’s women are contributing to family and nation’s economy. This study proposed a new conceptual framework that incorporates the importance of the worklife balance and implication on health for women entrepreneurs in Small Medium Enterprises (SMESs). Survey questionnaire was used to gather information on variables that are pertinent to the development of the model. The survey questionnaires were analyzed using multiple regression. The samples for this study consisted of 278 women entrepreneurs. The findings revealed that work-life balance women entrepreneurs model (WLBWE model) is suitable for women entrepreneurs to enhance their life well – being and gain profit in their business. Finally, the alert of health affected only significant in the contribution between work demands and family demands to enhance profit in organization and maintain with happy life with family and doesn’t give a direct impact to personal and annual turnover performance. The study is beneficial for policy makers and Human Capital Development units in organizations to embed essential concepts in their organizations’ strategic planning.